Attitudes to Patients’ Safety Questionnaire in The Arabic Context: Psychometric Properties - Muayyad Ahmad; Bushra Ghannam (Fakultas Ilmu Keperawatan Universitas Indonesia, 2024)
Patient safety education is often implicit in undergraduate nursing curricula, making it harder to meet competency standards. The Attitudes to Patient Safety Questionnaire (APSQ-III), which was developed in 2009 by Carruthers and collaborators in the United Kingdom, examines patient safety on a more sophisticated system level and has the potential to lead productive, nonhierarchical collaboration in educational settings. This study's goal was to use rigorous psychometric testing to validate the Arabic version of the Attitudes to Patient Safety Questionnaire (APSQ-III) for nursing students in an Arabic context. The majority of the 217 students recruited for this study through a convenience sampling technique were in their fourth year of college. There were two phases of APSQ-III validation investigations. Initially, three nurses were hired. The team documented their ideas and selected the best one. The Arabic version of the APSQ-III was translated using World Health Organization (WHO) principles. A number of models were developed and evaluated. On the APSQ-III, which had a total of 25 questions, a principal components analysis with equamax rotation was carried out. The analysis revealed that the six higher-order factors with respective eigenvalues of (5.9, 3.1, 2.0, 1.3, 1.2, and 1.1) account for 58.4% of the total variance. All resulting factors contained at least three variables with clean loadings. The APSQ-III, which has been modified for use with nursing students in Jordan and other Arab countries has achieved construct validity and a Cronbach’s alpha reliability of 0.80 for measuring attitudes regarding patient safety. Keywords: Arab, attitudes, patients, safety, validation Abstrak Kuesioner Sikap terhadap Keselamatan Pasien dalam Konteks Arab: Psychometric Properties. Pendidikan keselamatan pasien sering kali tidak tersirat dalam kurikulum sarjana keperawatan, sehingga lebih sulit untuk memenuhi standar kompetensi. Attitudes to Patient Safety Questionnaire (APSQ-III), yang dikembangkan oleh Carruthers dan kolaboratornya pada tahun 2009 di Inggris, meneliti keselamatan pasien pada tingkat sistem yang lebih canggih dan memiliki potensi untuk menghasilkan kolaborasi yang produktif dan tidak hirarkis dalam lingkungan pendidikan. Tujuan dari penelitian ini adalah untuk memvalidasi versi bahasa Arab dari APSQ-III untuk mahasiswa keperawatan dalam konteks bahasa Arab, dengan menggunakan pengujian psikometrik yang ketat. Mayoritas dari 217 mahasiswa yang direkrut melalui convenience sampling technique, berada di tahun keempat kuliah. Ada dua tahap investigasi validasi APSQ-III. Awalnya, tiga orang perawat direkrut. Tim mendokumentasikan ide-ide mereka dan memilih yang terbaik. Versi bahasa Arab dari APSQ-III diterjemahkan dengan menggunakan prinsip-prinsip WHO. Sejumlah model dikembangkan dan dievaluasi. Pada APSQ-III, yang memiliki total 25 pertanyaan, dilakukan analisis komponen utama dengan rotasi equamax. Analisis tersebut menunjukkan bahwa enam faktor tingkat tinggi dengan nilai eigen masing-masing (5.9, 3.1, 2.0, 1.3, 1.2, dan 1.1), menyumbang 58.4% dari total varian. Semua faktor yang dihasilkan mengandung setidaknya tiga variabel dengan clean loadings. APSQ-III, yang telah dimodifikasi untuk digunakan mahasiswa keperawatan di Yordania dan negara-negara Arab lainnya, telah mencapai validitas konstruk dan reliabilitas Cronbach's alpha sebesar 0,80 untuk mengukur sikap terkait keselamatan pasien. Kata Kunci: Arab, keselamatan, pasien, sikap, validasi